PENGOLAH AIR LIMBAH PABRIK TAHU DI KOTA PADANGMENGGUNAKAN AKTIF DARI BAMBU BETUNG - Delvina, Mery (journal of residu, 2019)
1   Tofu industry wastewater originates from soybean washing and soaking processes, as well as pressing and printing processes. Besides that, it is also sourced from the rest of the washing process for the equipment used. Liquid waste contains high Total Suspended Solid (TSS), Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD) and with the amount of pollutants present in waste water, the oxygen level will decrease. Thus it will cause life in the waters that need oxygen to be disrupted. One method used to remove pollutants from wastewater is adsorption. Adsorption is an absorption event of an adsorbate on the surface of the adsorbent. Adsorbates are substances (molecules, atoms, or ions) that are absorbed while the adsorbent is a substance that absorbs. The adsorbent that is often used to reduce concentration is activated carbon, because it is easier to obtain commercially.